National Essential Public Health Services Programs over the Past Decade Research Report One：Significance and Experiences of Implementing National Essential Public Health Services Programs - Lili YOU, Yuanli LIU (Zhongguo quanke yixue, 2022)
The National Essential Public Health Services Programs (NEPHSP) is a systematic and overall basic public service system arrangement made by the Chinese government at the national level aiming at the main health problems existing in urban and rural residents and targeting at key population key diseases and the whole population. Year of 2019 is the tenth anniversary of the NEPHSP implementation. This article summarized the significance of implementing NEPHSP based on a 10-year evaluation of NEPHSP from four aspects: universal health coverage, Healthy China 2030 strategy, China's deepening health system reform and major institutional innovation. At the same time, several main experiences of successful projects were summarized, including the following five aspects: establishing and improving a strong project organization and management system, steadily increasing strength of financial support, following the principle of gradual implementation of projects, advocating and encouraging local exploration in accordance with local conditions, and adhering to clear reward and punishment performance appraisal. From the historical perspective, this paper summarized the implementation of the great project led by the Chinese government in order to introduce the Chinese way, Chinese practice and Chinese experience of primary health care work in the new era at home and abroad.